Hepatic Hemangioma: An Unusual Cause of Fever of Unknown Origin - Kathleen Hopkins; Robert J Bailey (Canadian Journal of Gastroenterology)
A patient with a giant cavernous hemangioma of the liver presented with fever of unknown origin. Extensive investigation revealed no other source of temperature. Following surgical resection of the Lesion the fever resolved. Pathology of the benign cavernous hemangioma showed only areas of thrombosis.